2013
DOI: 10.1051/0004-6361/201322083
|View full text |Cite
|
Sign up to set email alerts
|

Preplanetary scavengers: Growing tall in dust collisions

Abstract: Dust collisions in protoplanetary disks are one means to grow planetesimals, but the destructive or constructive nature of high speed collisions is still unsettled. In laboratory experiments, we study the self-consistent evolution of a target upon continuous impacts of submm dust aggregates at collision velocities of up to 71 m/s. Earlier studies analyzed individual collisions, which were more speculative for high velocities and low projectile masses. Here, we confirm earlier findings that high speed collision… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 62 publications
2
30
2
1
Order By: Relevance
“…2(b), dem onstrate that the global filling factor (0) increases roughly linearly w ith impact velocity v, (< P ) -(0)o +av. (7) The linear increase w ith velocity is in line with recent experim ents perform ed on agglom erate form ation by im pacts o f subm illim eter dust aggregates [21]; these authors find a linear increase o f the average filling factor o f the aggregate at im pact velocities below 10 m /s. The fit factors a and (0}o are assem bled in Table I.…”
Section: A Compactionsupporting
confidence: 86%
See 1 more Smart Citation
“…2(b), dem onstrate that the global filling factor (0) increases roughly linearly w ith impact velocity v, (< P ) -(0)o +av. (7) The linear increase w ith velocity is in line with recent experim ents perform ed on agglom erate form ation by im pacts o f subm illim eter dust aggregates [21]; these authors find a linear increase o f the average filling factor o f the aggregate at im pact velocities below 10 m /s. The fit factors a and (0}o are assem bled in Table I.…”
Section: A Compactionsupporting
confidence: 86%
“…C ollisions o f relatively large * urbassek@rhrk.uni-kl.de; http://www.physik.uni-kl.de/urbassek/ (i.e., up to centim eter-sized) projectiles and targets were recently perform ed [18,19], Experim ents o f centim eter-sized aggregates [20] show ed that highly porous dust aggregates can retain their highly porous cores if collisions are highly energetic w ith collisions in the order o f m agnitude o f 6 m /s and a dense shell form s on top o f the porous core. M eisner et al [21] studied agglom erate form ation by im pacts of subm illim eter dust aggregates and found that the agglom erate density increases with speed and reaches values o f up to 38% at 49 m /s im pact speed.…”
Section: Introductionmentioning
confidence: 99%
“…These velocities are considerably higher than our results. However, the size regime is completely different: The size of the projectiles used by Meisner et al (2013) is comparable to the size of our target aggregates. Since the maximum value for v A→E is limited by the onset of fragmentation we expect to observe accretion at higher velocities when using cm-to decimetersized target aggregates.…”
Section: Influence Of the Projectile Sizementioning
confidence: 90%
“…Recently, Meisner et al (2013) studied high velocity impacts of SiO 2 dust aggregates and found that growth is possible at velocities of ≈70 ms −1 . These velocities are considerably higher than our results.…”
Section: Influence Of the Projectile Sizementioning
confidence: 99%
“…Collisional grain charging is one such mechanism (Poppe et al 2000a,b); however, this is only possible for small particles, so it is unlikely that planetesimals can form by this mechanism alone (Blum 2010). Growth has also been demonstrated through mass transfer (Wurm et al 2005;Teiser & Wurm 2009b,a;Kothe et al 2010;Teiser et al 2011;Windmark et al 2012a,b;Garaud et al 2013;Meisner et al 2013), but owing to the increasing relative velocities of larger particles mentioned earlier and the importance of erosion (Schräpler & Blum 2011;Seizinger et al 2013), it is unclear whether this can account for growth beyond centimetre sizes.…”
Section: Introductionmentioning
confidence: 99%